THE INFLUENCE OF SELF-CONCEPT AND PARENTING PATTERNS ON BULLYING BEHAVIOR AT SMA X - Dita Hairia; Risydah Fadilah; Siti Aisyah (RADJA PUBLIKA, 2024)
This research aims to determine the influence of self-concept and parenting patterns on bullying behavior at SMA The sampling technique used was purposive sampling technique. Data collection was carried out using a Likert scale with three scales, namely the bullying behavior scale, self-concept scale and parenting style scale. Based on the results of product moment correlation analysis calculations, it can be seen that: (1) there is a significant negative relationship between self-concept and bullying behavior as determined by the coefficient R = -0.392 (2) there is a significant negative relationship between parenting style and bullying behavior as determined by coefficient R = -0.834 (3) there is a significant negative relationship between self-concept and parenting patterns on bullying behavior at SMA X as shown by R-Square = 0.741 with a contribution of 74.1%. From the results of the research conductedthen it can be concluded that the proposed hypothesis is accepted.